INTERCONNECTIONS BETWEEN IDENTITY CO-CONSTRUCTION AND IMPOLITENESS IN AMERICAN FAMILY DISCOURSE - Khukhunaishvili, Mari (Online Journal of Humanities ETAGTSU, 2018)
Based on the principles of Discursive, i.e. Genre approach to Im/politeness, under which both identity construction and impoliteness assessments are inextricably linked to particular genre conventions, the aim of this paper is to observe interconnections between identity co-construction and impoliteness in American family discourse. Studying family discourse is important not only from the point of identity coconstruction and human socialization but also due to the fact that the conflicts and strategies detected in verbal interaction in the family setting are found in wider society. The research is grounded on the study of the verbal interaction in American pseudo-documentary TV series "Modern Family". The sequences in the data include verbal interaction between judgmental, hot-tempered, loud Jay Pritchett - the oldest member of the family- and other family members. This article provides a close analysis of linguistic resources used by Jay to construct his local identities and looks at the role of impoliteness in the process of identity co-construction within the family discourse. The theoretical basis for the research combines the Socio-constructivist approaches to identity construction, and Discursive, i.e. Genre approach to the study of Im/politeness. Full Text (PDF)